Anti-Tumor Necrosis Factor-α Use in Pediatric Inflammatory Bowel Disease—Reports from a Romanian Center - Roxana Matran; Andra-Mihaela Diaconu; Andreea Maria Iordache; Irina Dijmărescu; Alexandra Coroleucă; Daniela Păcurar; Cristina Becheanu (Pharmaceuticals)
Background/Objectives: The introduction of anti-tumor necrosis factor-α (anti-TNF-α) agents, particularly infliximab (IFX) and adalimumab (ADA), has significantly expanded the therapeutic arsenal for inflammatory bowel disease (IBD). While these biologics have demonstrated substantial efficacy, they are associated with a spectrum of potential adverse events (AEs). This study aims to evaluate and document these AEs to facilitate optimal patient selection and monitoring strategies of patients undergoing these therapies. Methods: This retrospective, single-center study examined pediatric IBD patients receiving anti-TNF-α therapy at the “Grigore Alexandrescu” Emergency Hospital for Children in Bucharest, Romania, from January 2015 to October 2024. AEs were categorized into non-infectious complications (acute infusion reactions, anti-drug antibody formation), dermatological effects (erythema nodosum, vasculitis), neurological effects (Guillain–Barré syndrome), and infections. AEs were analyzed in relation to the specific anti-TNF-α agent administered and comprehensively characterized. Results: Of 40 patients enrolled, 22 (55%) had Crohn’s disease (CD). The median (IQR) age at diagnosis was 14.8 years [10.8–15.9]. IFX was used in 34 (85%) patients while 6 (15%) patients received either ADA or IFX/ADA sequential therapy. Twenty-seven AEs were documented in 19 (47.5%) patients, the most prevalent being antidrug antibody formation (44.4%), infections (22.2%), and acute infusion reactions (22.2%). All ADA-exposed patients experienced at least one AE, compared to 41.2% (n = 14) patients treated with IFX, p = 0.01. Conclusions: AEs were observed in approximately half of the study cohort, with anti-drug antibody formation emerging as the most frequent complication. ADA therapy was associated with a significantly higher rate of AEs compared to IFX. These findings underscore the critical importance of vigilant monitoring for patients undergoing anti-TNF-α therapy in pediatric IBD management.